University Violence and its Relationship to Irrational Ideas and Methods of Family Upbringing Among a Sample of Palestinian University Students (Al-Quds Open University as a Model) - Atiya, Mai Hassan; Abu Shakra, Saeeda Muhammad (Journal of Educational and Psychological Sciences, 2023)
The study aims to reveal the relationship between university violence and its relationship to irrational ideas and methods of socialization among a sample of Palestinian university students. The study uses the descriptive correlative approach, and to achieve the objectives of the study, scales were applied: the University Violence Scale by Asfour and Nimr (2012), the Rihani Irrational Ideas Scale (1985), and the Raqb and Zayd Family Upbringing Scale (2008), on a sample of (203) university students from Al-Quds University open, The results show that there is a statistically significant correlation between university violence and irrational thoughts and family upbringing among a sample of Palestinian university students, and the results also indicate that the degree of violence among university students is low, where it was at a rate of (37.4%)، while the results reveal that the degree of irrational thinking among students is at a rate of (71.2%), and (66.6%) of family upbringing contributes to its appearance among students. While the results also appear; The contribution of irrational ideas and family upbringing to university violence, and the results reveal that the moral regression model through the value of (q) of (1.873) and the results explain that irrational ideas and family upbringing contribute to explaining (18%) of the variance in university violence, The study recommends the necessity of working programs of guidance programs based on cognitive-behavioral counseling and rational cognitive counseling to change the irrational ideas of students in universities.